The new age of ethical marketing for the 21st century - Halpern, David (International journal of value-based management, 1993)
The premise of this paper is that the strong trends toward ever increasing centralization in the agricultural producing sector of the United States in the 1980s will exacerbate in the middle-to-late 1990s. This, in turn, will lead to both radical changes in the consumer movement by the year 2000, and also to a completely redefined mission for the corporate marketing function as well., Specifically, the deliberate federal policies of the 1980s which led to a “shake-out” of the small family farm units in favor of large agri-business concerns in order to reduce federal subsidies will lead, in the 1990s, to the most noted of deleterious consequences of monopolization, namely ever increasing prices and lowered quality. The authors believe that by the late 1990s the American public will perceive this state of affairs as being intolerable and it will lead them to organize “Big Consumerism”, a cohesive, much strengthened version of the consumer movement of the 1980s. This movement will, among other major activities, establish consumer cooperatives as a way to control costs through the elimination of unnecessary middlemen., In addition, this new consumerism will demand a change in the ethical standards of business behavior which, in turn, will result in a reformation in the role of the “New Marketer”. This “New Marketer” function will be envisioned and practiced by incumbents as informational and educational, adhering to the highest standards of truthfulness concerning the products they are attempting to market. In this regard, the role of governmental agencies will be greatly strengthened and expanded to insure that the marketing profession lives up to these highest ethical standards and practices.